The Relationship of Stress to Blood Sugar Levels of Diabetic Mellitus Patients in the Bernung Health Center, Pesawaran Regency - Mulia, Madepan (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background : Diabetes mellitus is a metabolic disorder with increased blood glucose levels due to impaired insulin secretion, insulin action or both. Diabetes mellitus is characterized by high blood sugar levels as a result of insulin function insufficiency which can be caused by impaired or deficient insulin production by beta Langerhans cells of the pancreas or by the body's cells being less responsive to insulin. Stress is a condition when there is a discrepancy between expectations and reality. Stress and diabetes mellitus have a close relationship. Objective : The purpose of this study was to determine the relationship between stress and blood sugar levels in patients with diabetes mellitus in the Bernung Community Health Center Working Area, Pesawaran Regency. Method : This is a quantitative analytical research with a cross-sectional approach. This study was conducted on 30 patients with diabetes mellitus, using a questionnaire. The tool used in this study was a stress level questionnaire which was measured using the Perceive Stress Scale (PSS) questionnaire. It is said that mild stress has a score of 0-13, moderate stress has a score of 14-26, and severe stress has a score of 27-40. While blood sugar levels are obtained by measuring the patient's blood sugar using the Instant Glucotest EasyTouch GCU 3 in 1. Blood sugar levels are expressed in mg/dL. To test the relationship, an analysis was used using the Chi-Square test with a confidence value of 95% and a significance of 0.05. Result : The results of the study showed that there was a relationship between stress and blood sugar levels of diabetes mellitus patients (p=0.000). Conclusion : Based on the results of the study, it was found that there was a relationship between stress and blood sugar levels of diabetes mellitus patients in the Bernung Health Center Work Area, Pesawaran Regency.